Phoenixin: uncovering its receptor, signaling and functions - McIlwraith Emma K; BELSHAM Denise D (Acta Pharmacologica Sinica, 2018)
Abstract Phoenixin (PNX) is a newly discovered peptide that has been linked to reproductive function, both in the hypothalamus and pituitary. This review will focus on the most recent discoveries related to this novel neuropeptide. Initially, it was found that PNX increased gonadotropin releasing hormone (GnRH)-stimulated luteinizing hormone (LH) release from pituitary cells. Importantly, knockdown of PNX in female rats extended the estrous cycle by 2.3 days. Using novel hypothalamic cell lines, we found that PNX has a stimulatory role on kisspeptin (Kiss) and GnRH gene expression and secretion. The PNX receptor was uncovered using siRNA knockdown of GPR173, an orphan receptor postulated to bind PNX. We have found that the PNX-R signaling through protein kinase A (PKA) in hypothalamic neurons. Althuogh a number of studies demonstrate that PNX plays an important role in reproductive function, there is also evidence that it may have other functions, regulating the heart, feeding, memory, and anxiety, both in the brain and the periphery.